Matrine prevents bone loss in ovariectomized mice by inhibiting RANKL-induced osteoclastogenesis - Chen, Xiao (FASEB J, 2017)
Osteoporosis is a metabolic bone disease characterized by decreased bone density and strength due to excessive loss of bone protein and mineral content. The imbalance between osteogenesis by osteoblasts and osteoclastogenesis by osteoclasts contributes to the pathogenesis of postmenopausal osteoporosis. Estrogen withdrawal leads to increased levels of proinflammatory cytokines. Overactivated osteoclasts by inflammation play a vital role in the imbalance. Matrine is an alkaloid found in plants from the Sophora genus with various pharmacological effects, including anti-inflammatory activity. Here we demonstrate that matrine significantly prevented ovariectomy-induced bone loss and inhibited osteoclastogenesis in vivo with decreased serum levels of TRAcp5b, TNF-α, and IL-6. In vitro matrine significantly inhibited osteoclast differentiation induced by receptor activator for NF-κB ligand (RANKL) and M-CSF in bone marrow monocytes and RAW264.7 cells as demonstrated by tartrate-resistant acid phosphatase (TRAP) staining and actin-ring formation as well as bone resorption through pit formation assays. For molecular mechanisms, matrine abrogated RANKL-induced activation of NF-κB, AKT, and MAPK pathways and suppressed osteoclastogenesis-related marker expression, including matrix metalloproteinase 9, NFATc1, TRAP, C-Src, and cathepsin K. Our study demonstrates that matrine inhibits osteoclastogenesis through modulation of multiple pathways and that matrine is a promising agent in the treatment of osteoclast-related diseases such as osteoporosis.—Chen, X., Zhi, X., Pan, P., Cui, J., Cao, L., Weng, W., Zhou, Q., Wang, L., Zhai, X. Zhao, Q., Hu, H., Huang, B., Su, J. Matrine prevents bone loss in ovariectomized mice by inhibiting RANKL-induced osteoclastogenesis.